HTLV-1-associated infective dermatitis demonstrates low frequency of FOXP3-positive T-regulatory lymphocytes. Issue 3 (March 2015) - Torres-Cabala, Carlos A; Curry, Jonathan L; Li Ning Tapia, Elsa ML; Ramos, Cesar; Tetzlaff, Michael T; Prieto, Victor G; Miranda, Roberto N; Bravo, Francisco
Highlights: The pathogenesis of HTLV-1-associated infective dermatitis (ID)() is unclear. Patients with ID may subsequently present with ATLL and/or HAM/TSP. ID histopathology overlaps with lymphoid reactive and neoplastic proliferations. ID demonstrates low frequency of Tregs as opposed to other inflammatory conditions. Decreased numbers of Tregs may have a role in the pathogenesis of this disease. Abstract: Background : Human T-lymphotropic virus (HTLV)-1-associated infective dermatitis (ID) is a rare severe chronic eczema, considered as a harbinger for the development of cutaneous adult T-cell leukemia/lymphoma (ATLL) and/or HTLV-1-associated myelopathy (HAM)/tropical spastic paraparesis (TSP). The pathogenesis of ID remains unclear. High numbers of peripheral blood CD4+ CD25+ FoxP3+ regulatory T cells (Tregs) have been reported in ATLL and HAM/TSP. Objective : To investigate the status of Tregs, unknown to date, and the histopathological features of ID. Methods : We studied 16 skin biopsies from 15 Peruvian adults and children with ID by immunohistochemistry. Results : Histopathological patterns were seborrheic dermatitis-like and lichenoid. Intraepidermal lymphocytes were conspicuous. The infiltrate was composed of a CD3+ T cell infiltrate with a predominance of CD8+ over CD4+ cells. CD4+ CD25+ FoxP3+ Tregs were rare and their numbers were significantly lower than those reported in other inflammatory dermatoses. Conclusion : Tregs have an essential role in maintaining immune homeostasis of skin. Treg dysregulation ends in severe clinical manifestations. The clinical presentation of ID, with lesions resembling those seen in patients with atopic dermatitis and with mutations in the FoxP3 gene, is in agreement with a common Treg-deficient skin environment in these disorders, possibly secondary to HTLV-1 infection.